Botanical drug products : recent developments and market trends - Lokhande, Jayant N.; Pathak, Yashwant (Boca Raton, FL : CRC Press, 2019)
Botanicals, which have been part of human food and medicine for thousands of years, are perceived as being safer than synthetic pharmaceuticals. The global botanical drug market was expected to reach $26.6 billion by 2017. In terms of FDA regulations, botanical drugs are no different from non-botanical products, having to meet the safety and effectiveness standards of a new drug in accordance. This book comprises a complete start-to-end process from drug-idea conception, to drug development process.
OCLC-licensed vendor bibliographic record.
Keywords: Materia medica, Vegetable; Drug development; MEDICAL / Pharmacology; HEALTH & FITNESS / Herbal Medications; SCIENCE / Chemistry / General; TECHNOLOGY / Food Science